Brain patterning perturbations following PTEN loss - Veleva-Rotse, Biliana O.; Barnes, Anthony P. (Frontiers in Molecular Neuroscience, 2014)
This review will consider the impact of compromised PTEN signaling in brain patterning. We approach understanding the contribution of PTEN to nervous system development by surveying the findings from the numerous genetic loss-of-function models that have been generated as well as other forms of PTEN inactivation. By exploring the developmental programs influenced by this central transduction molecule, we can begin to understand the molecular mechanisms that shape the developing brain. A wealth of data indicates that PTEN plays critical roles in a variety of stages during brain development. Many of them are considered here including: stem cell proliferation, fate determination, polarity, migration, process outgrowth, myelination and somatic hypertrophy. In many of these contexts, it is clear that PTEN phosphatase activity contributes to the observed effects of genetic deletion or depletion, however recent studies have also ascribed non-catalytic functions to PTEN in regulating cell function. We also explore the potential impact this alternative pool of PTEN may have on the developing brain. Together, these elements begin to form a clearer picture of how PTEN contributes to the emergence of brain structure and binds form and function in the nervous system.